Cluster activities in different institutional environments: Case studies of ICT-clusters from Austria, Germany, Ukraine and Serbia - Anastasiia Konstantynova; Tine Lehmann (Administrative Sciences, 2017)
In recent decades, numerous cluster associations with public and/or private support have been established to facilitate clusters. These cluster associations have launched a number of activities and services aiming to increase the competitiveness, innovation, and productivity of their members and beyond. At the same time, it appears that many of these associations apply similar activity bundles to reach their objectives. However, the institutional context differs between clusters and their countries. This paper questions how these activity bundles are influenced by different sets of institutional conditions and proposes a framework for the explorative analysis of cluster activity bundles in specific institutional environments. Moreover, using the framework, a detailed review of cluster associations and their activities in different information and communication technologies (ICT) clusters is presented, the development of which is central to regional advanced industrial transformation in the context of regional smart specialization and the Industrial Renaissance.
Keywords: 350; clusters; cluster policy; cluster association; institutions; ICT